P80 Meeting urological cancer targets during Covid-19. (8th April 2021) - Dirie, J; Hart, E; Mahesan, T; Fawcett, W; Perry, M; Janardanan, S; Moschonas, D; Krishnaji, P; Abou-Chedid, W
Abstract: Introduction & Objectives: The pandemic caused by Covid-19 has caused significant strain on healthcare professionals across the globe. Without downplaying the devastating effects of the virus itself, the collateral damage – specifically in cancer targets – has only compounded an already difficult time in medicine. Therefore, it was of the utmost importance that we: strived to continue to meet our cancer targets, and we analysed our success in addressing this. Materials & Methods: A key factor was the proximity of a private Nuffield hospital (GN) to the primary trust. GN acted as a 'clean site'. From 6th April 2020, 2 Xi Da Vinci robots and dedicated staff were relocated to day surgery theatres with direct: access to GN. Endoscopic procedures occurred in GN theatres. Post-operative recovery happened in GN. National guidelines were followed including COVID-19 symptom screening, isolation and preoperative nasopharyngeal swabs. All theatre staff were swabbed weekly and worked solely at GN. Patients were risk stratified prior to admittance. Cancer features and patient risk factors for COVID-19 were taken into account. Standard enhanced recovery principles were applied throughout the patient's journey. In theatre, we worked to ensure minimal staff numbers for safe practice were present. We reviewed operations performed, alongside cancer (prostate & bladder) pathway data from March to June 2020. For comparison identical data from August to November 2019 was collected. Results: There were a total of 369 cancer operations performed at our Trust from March until June 2020. In comparison, 407 cancer operations were performed in the 4 months from August until November 2019. For both timeframes, a: variety of robotic, endoscopic and open surgeries were carried, with similar numbers seen in each. In total, we received 80 referrals for possible prostate malignancies from March – June 2020, and 150 from August – November 2019. Days to MRI was slightly better in March to June, but we did not find a statistical difference. We: found a statistically significant decrease in the number of days it took for a patient to go from referral to diagnosis. Furthermore, we also improved on the proportion of patients who had their diagnosis told to them within 28 days, from 74% to 87%. In total, we received 134 referrals for possible bladder malignancies from March – June 2020, and 81 from August – November 2019. We improved on days to OPA for patients and time to flexible cystoscopy, with both results carrying statistical significance. We were able to reduce time to OPA from 8 to 6 days, and time to flexible cystoscopy from 26 to 12 days. Conclusions: This study demonstrates that with rapid development of separate 'clean' and 'COVID' sites, we successfully delivered a comparable, safe and effective cancer service. As we potentially face a second wave we share our success to see if these changes can be replicated elsewhere.